Design of Arduino Uno-Based Height and Weight Measuring Instrument for Initial Screening of Stunting Cases - Hayuningclara, Talitha Nabila (Jurnal Fisika dan Aplikasinya, 2024)
Monitoring nutritional status in toddlers is very important because it can be an early indicator of possible health problems in children. Currently, the process of monitoring children's nutrition is generally still carried out manually, which not only takes longer but is also less efficient in practice. To overcome the limitations of conventional measuring devices, a digital measuring device for height and weight was designed. This tool displays the results of height and weight measurements simultaneously on an LCD (liquid crystal display) screen. This tool works with uses an Arduino microcontroller as a control center and uses electronic sensors, namely the HC-SR07 ultrasonic sensor to measure height and the HX711 loadcell sensor to measure weight. From the data obtained, the error value and accuracy of the loadcell sensor after calibration produced an error value of 6.24% and an accuracy of 93.76%. Meanwhile, the ultrasonic sensor test results after the calibration process produced an error value of 0.052% and an accuracy of 99.94%.